SKETSA MASYARAKAT PEMULUNG KOTA BANDUNG - Siti Kusumawati Azhari (Jurnal Sosioteknologi, 2009)
Scavengers refer to people that have an activity of collecting used things. They are workforces that have low payment by industries. Their activity is not protected and developed by the Department of Manpower because it does not have work relation and guarantee of work continuity. The purpose of this research is to obtain the data of social economic life of scavengers in Bandung City, study their social life, and analyze the research findings. Descriptive method is applied in this research, and direct field observation is done to collect data through questionnaires. The results show that scavenging is generally their permanent employment; their average age are above 25 years, and primary school graduates. They generally live by hiring or joining in shed, and they are Sundanese and Moslems. They are generally married and have two children. They do not receive neither Government's nor NGO's aids. Ironically, one third of the scavengers are smokers that can consume one pack cigarettes and more a day.